2017
DOI: 10.1155/2017/6174743
|View full text |Cite
|
Sign up to set email alerts
|

Viral Hepatitis Endemicity and Trends among an Asymptomatic Adult Population in Ho: A 5-Year Retrospective Study at the Ho Municipal Hospital, Ghana

Abstract: Background Using prospective blood donors as a proxy, this study was aimed at estimating the burden and five-year (2012–2016) trend of viral hepatitis (HBV and HCV) infection among asymptomatic adult population in Ho. Materials and Methods A retrospective analysis was done on secondary data extracted from the hospital archives comprising 4,180 prospective blood donors from January 2012 to December 2016. Demographic variables included age and sex, as well as place of residence. Screening results of serum infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
8
5
Order By: Relevance
“…These HBV and or HCV seroprevalence patterns are not different from previous studies from Ghana that involved the general population (i.e. HIV uninfected individuals) where the seroprevalences in most cases ranged from 6.94 to 15.8% for HBsAg and 1.84 to 8.4% for HCV [1417, 19]. Only two studies reported lower seroprevalences, 5.5% for HBsAg [18] and 0.4% for HCV [16].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…These HBV and or HCV seroprevalence patterns are not different from previous studies from Ghana that involved the general population (i.e. HIV uninfected individuals) where the seroprevalences in most cases ranged from 6.94 to 15.8% for HBsAg and 1.84 to 8.4% for HCV [1417, 19]. Only two studies reported lower seroprevalences, 5.5% for HBsAg [18] and 0.4% for HCV [16].…”
Section: Discussioncontrasting
confidence: 58%
“…However, in Ghana although HIV, HBV and HCV are public health issues, free HBV and HCV laboratory testing and treatment are not provided side-by-side HIV testing and treatment due to lack of resources and this might have negative effect on the efficacy of the regimens used to manage them. In Ghana, the estimated HIV prevalence is 1.47%, and that of HBV and HCV reported in the general population are 5.5–15.8% and 0.4–8.4% respectively [13–19]. However, studies on HBV and HCV among HIV infected individuals are limited and most of these studies were done at a single site, with HBV prevalence ranging from 2.4 to 41.7% while 1.0% has been reported for HCV [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…A total of three studies [32][33][34] reported HBV prevalence among blood donors with a total sample size of 16 192 participants. The hepatitis B prevalence ranged from 6.94% to 7.50% with a pooled prevalence of 7.17% (CI: 6.78-7.57) (S3 Appendix).…”
Section: Prevalence Of Hepatitis B Among Blood Donorsmentioning
confidence: 99%
“…The disease has been documented to cause between 600,000 to 800,000 deaths every year [3,[7][8][9][10] . In Sub-Saharan Africa, about 8% of the population are chronic carriers of HBV with the highest rate of 2.8% in the West African sub-region including Ghana where an estimated national prevalence of 12.3% in a systemic review has been documented [11] . Infection with Hepatitis C virus (HCV) and the associated pathological outcome are analogous to those of HBV infection.…”
Section: Introductionmentioning
confidence: 99%